1977
DOI: 10.1148/123.2.291
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Radiographic Features of Aberrant Pancreatic Rests Involving the Stomach

Abstract: The radiographic features of 20 cases of pathologically confirmed heterotopic pancreatic rests involving the stomach were analyzed. Aberrant pancreatic tissue in the stomach produces a broader spectrum of radiographic findings than had been thought. The mass produced by the aberrant tissue is often larger and more sessile than usually anticipated, and may simulate a mural neoplasm or adenomatous polyp. While most cases occur in the distal antrum or prepyloric area, some occur in the more proximal portion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 2 publications
3
29
0
2
Order By: Relevance
“…Central umbilications are found in less than half of pancreatic rests, but would be expected to be a persistent finding once documented. Additionally myoepithelial hamarto-137 mas (adenomyomas), including pancreatic rests, are generally not diagnosed in infancy [6]. Feldman and Weinberg reported that most accessory pancreatic nodules are only 1 to 2 mm in diameter in neonates [7].…”
Section: Discussionmentioning
confidence: 99%
“…Central umbilications are found in less than half of pancreatic rests, but would be expected to be a persistent finding once documented. Additionally myoepithelial hamarto-137 mas (adenomyomas), including pancreatic rests, are generally not diagnosed in infancy [6]. Feldman and Weinberg reported that most accessory pancreatic nodules are only 1 to 2 mm in diameter in neonates [7].…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that in our case, obesity and diabetes mellitus were significant etiologic factors responsible (7,8). Hepatic disease, chronic pancreatitis and adultonset diabetes mellitus may have been contributory (7,8).…”
mentioning
confidence: 54%
“…Fatty replacement of pancreas may be uniform or may be unevenly distributed, and Langerhans are usually not affected by fatty replacement (4). No etiology has been established for fat replacement of the pancreas; however, several predisposing factors have been suggested: age, obesity, diabetes mellitus, chronic pancreatitis, hepatic disease, dietary deficiency, viral infection, steroid therapy, obstruction of the pancreatic duct, and fibrocystic disease (7,8). Experimental and clinical studies have shown that fat replacement of the pancreas does result from ligation of the pancreatic duct or obstruction of the pancreatic duct by a tumor or a calculus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant tissue consists of endoderm that is composed of all the cell types normally found in the pancreas, and it often includes islets of Langerhans. Consequently, pancreatitis with fat necrosis, islet cell tumors with hyperinsulinism and pancreatic carcioma with metastases may occur in heterotopic pancreas (6). Symptoms rarely come into existence with the presence of heterotopic pancreatic tissue alone.…”
Section: Discussionmentioning
confidence: 99%